CT depiction of ovarian dermoid showing spontaneous fistulous communication with small bowel - Richa Singh Chauhan; Ishan Kumar; Ashish Verma (The Egyptian Journal of Radiology and Nuclear Medicine, 2018)
Dermoidcysts of the ovary represent the most common form of benign ovarian tumors. Their site, size and clinical presentations are extremely variablecausing confusion with various medical and surgical entities. Uncomplicated dermoid cysts are often asymptomatic andare relatively easy to diagnose on imaging. Symptomatic complicated dermoids may lead to diagnostic dilemmas. Of the various complications of ovarian dermoid, spontaneous rupture into theadjacent viscera is the least common. We report a case of a 55-year-old patient presenting with abdominal pain and passage of hair-like and cheesy material in stools, in which contrast enhanced CT scan demonstrated bilateral ovarian dermoids with the right oneruptured into asmall bowel loop. Keywords: Ovarian dermoid, Cystic teratoma, Bowel infiltration, Fistula, Computed tomography